THE CHANGING CONSTITUTION IN INDONESIA AND THE UNITED KINGDOM: A COMPARATIVE STUDY - Laely Nurhidayah (LIPI Press, 2006)
Title of Book : The Changing Constitution Fourth Edition Edited By : Jeffrey Jowell and Dawn Oliver Year Published : 2000 Number of Pages : 387